HUBUNGAN TINGKAT PENGETAHUAN KADER KESEHATAN BERDASARKAN ANALISIS DATA PADA BALITA STUNTING MELALUI INOVASI PUDING DAUN KELOR DALAM UPAYA PENCEGAHAN STUNTING - Riansih, Chici; W Utami, Nugrahaningtyas; Yani Noor, Ahmad; Nur Seha, Harinto (Jurnal Permata Indonesia, 2024)
Background: Stunting in toddlers has an impact on child development. Empowering health cadres through stunting data analysis and nutritional innovations such as moringa pudding is important for stunting prevention. Objective: To assess the relationship between health cadres' knowledge of stunting data and the application of moringa pudding. Methods: Cross-sectional quantitative study on 50 cadres in Manisrenggo, Klaten. Data were collected by interview and questionnaire, analyzed using Chi-Square test. Results: 46% of cadres had good knowledge and 54% had fair knowledge. All cadres with good knowledge implemented moringa pudding. Chi-Square test results showed a significant association (p = 0.000). Conclusion: Cadre knowledge of stunting data is associated with the application of moringa leaf pudding in stunting prevention.